The dog in the freezer : three novellas - Mazer, Harry (New York : Aladdin Paperbacks, 1998)
Each of these three novellas looks at the relationship between a boy and a dog in a very different and unusual way. Includes "Giles' Song," a poem by Gina Mazer.
My life as a boy -- Puppy love -- The dog in the freezer.
4.8
5-8
Keywords: Dogs -- Fiction; Dogs -- Fiction